Study of the solar anisotropy of cosmic ray primaries of about 200 GeV energy with the L3+C muon detector - Dova, María Teresa (2008)
Context. Primary cosmic rays experience multiple deflections in the non-uniform galactic and heliospheric magnetic fields which may generate anisotropies. Aims. A study of anisotropies in the energy range between 100 and 500 GeV is performed. This energy range is not yet well explored. Methods. The L3 detector at the CERN electron-positron collider, LEP, is used for a study of the angular distribution of atmospheric muons with energies above 20 GeV. This distribution is used to investigate the isotropy of the time-dependent intensity of the primary cosmic-ray flux with a Fourier analysis. Results. A small deviation from isotropy at energies around 200 GeV is observed for the second harmonics at the solar frequency. No sidereal anisotropy is found at a level above 10-4 . The measurements were performed in the years 1999 and 2000.